Dynamics of the radix expansion map. (1994) - Goertzel, Ben; Bowman, Harold; Baker, Richard
Abstract : The chaotic dynamics of the mapϕ ( x ) = ( β x + α ) ( mod 1 ) are studied using Parry'sβ -expansion. It is shown that for1 < β < 2, a ≥ 0, the number of periodic points of periodn is0 ( β n ) .